Expert surveys in party research - Meijers, Maurits; Wiesehomeier, Nina (Taylor & Francis, 2023)
Expert surveys have become indispensable data resources in party research. This chapter takes stock of the developments of expert surveys on political parties, and looks ahead at the challenges that face expert survey research. We trace the expansion of this tool over the last 35 years for measuring not only political parties’ policy positions on a plethora of policy dimensions but also its increasing use to elicit judgements on non-policy-related party characteristics such as organisational features as well as parties’ attitudes towards issues pertaining to democracy and representation. The chapter furthermore reviews the ways in which the resulting data has been utilised in party research. Finally, we discuss the methodological challenges that expert survey projects must tackle in the future, with specific attention to problems concerning expert bias, cross-country comparability, and expert burden and fatigue.
Keywords: 59 Ciencia Política; ODS 16 - Paz, justicia e instituciones sólidas